Wild Voices: Mimicry, Reversal, Metaphor, and the Emergence of Language - Knight, Chris; Lewis, Jerome (Current Anthropology, 2017)
Why is it that, out of 220 primate species, we are the only one that talks? The relative inflexibility of primate vocal signaling reflects audience pressure for reliability. Where interests conflict, listeners? resistance to being deceived drives signalers to limit their vocal repertoire to signals that cannot be faked. This constraint was lifted in the human case, we argue, because the original victims of our species? first deceptive vocalizations were nonhuman animals. When our ancestors were vulnerable hominins equipped with limited weaponry, they kept predators away by increasing the range and diversity of their vocal calls. This led to choral singing, primarily by females, and deceptive mimicry of animal calls, primarily by scavenging and hunting males. A critical feature of our model is the core principle of reversal, whereby deceptive signals aimed originally by a coalition against an external target are subsequently redeployed for honest communicative purposes within the group. We argue that this dynamic culminated ultimately in gestural, vocal, and ritual metaphor, opening the way to word formation and the rapid emergence of grammar.Why is it that, out of 220 primate species, we are the only one that talks? The relative inflexibility of primate vocal signaling reflects audience pressure for reliability. Where interests conflict, listeners? resistance to being deceived drives signalers to limit their vocal repertoire to signals that cannot be faked. This constraint was lifted in the human case, we argue, because the original victims of our species? first deceptive vocalizations were nonhuman animals. When our ancestors were vulnerable hominins equipped with limited weaponry, they kept predators away by increasing the range and diversity of their vocal calls. This led to choral singing, primarily by females, and deceptive mimicry of animal calls, primarily by scavenging and hunting males. A critical feature of our model is the core principle of reversal, whereby deceptive signals aimed originally by a coalition against an external target are subsequently redeployed for honest communicative purposes within the group. We argue that this dynamic culminated ultimately in gestural, vocal, and ritual metaphor, opening the way to word formation and the rapid emergence of grammar.